Is Social Phobia a “Mis-Communication” Disorder? Brain Functional Connectivity during Face Perception Differs between Patients with Social Phobia and Healthy Control Subjects - Danti, Sabrina; Ricciardi, Emiliano; Gentili, Claudio; Gobbini, Maria Ida; Pietrini, Pietro; Guazzelli, Mario (Frontiers in Systems Neuroscience, 2010)
Recently, a differential recruitment of brain areas throughout the distributed neural system for face perception has been found in social phobic patients as compared to healthy control subjects. These functional abnormalities in social phobic patients extend beyond emotion-related brain areas, such as the amygdala, to include cortical networks that modulate attention and process other facial features, and they are also associated with an alteration of the task-related activation/deactivation trade-off. Functional connectivity is becoming a powerful tool to examine how components of large-scale distributed neural systems are coupled together while performing a specific function. This study was designed to determine whether functional connectivity networks among brain regions within the distributed system for face perception also would differ between social phobic patients and healthy controls. Data were obtained from eight social phobic patients and seven healthy controls by using functional magnetic resonance imaging (fMRI). Our findings indicated that social phobic patients and healthy controls have different patterns of functional connectivity across brain regions within both the core and the extended systems for face perception and the default mode network (DMN). To our knowledge, this is the first study that shows that functional connectivity during brain response to socially relevant stimuli differs between social phobic patients and healthy controls. These results expand our previous findings and indicate that brain functional changes in social phobic patients are not restricted to a single specific brain structure, but rather involve a mis-communication among different sensory and emotional processing brain areas.